Identification of three SNPs in smad4 gene by tetra‐primer ARMS PCR and analysis of their associations with growth traits in gynogenetic populations of Culter alburnus. (9th July 2020) - Chi, Meili; Jia, Yongyi; Yu, Junjian; Zheng, Jianbo; Liu, Shili; Cheng, Shun; Gu, Zhimin
Abstract: Three single nucleotide polymorphisms, c.1462C > T, c.1663G > T and c.2023G > A, in smad4 gene were isolated and typed in a normal population (meio‐G0), a first‐generation gynogenetic population (meio‐G1) and a second‐generation gynogenetic population (meio‐G2) in topmouth culter ( Culter alburnus ) by using the tetra‐primer amplification refractory mutation system (ARMS) PCR. The homozygosity of different loci in the three populations was analysed to study the efficiency of gene purification in this fish. Correlation of the three populations to seven growth traits (body length, body weight, body thickness, body height, total length, caudal peduncle length and caudal peduncle height) was estimated. Results showed that homozygosity and homozygosity rates of three SNP loci from meio‐G0 to meio‐G2 increased obviously, and the average homozygosity of c.1462C > T and c.1663G > T loci was 0.930 and 0.880 in meio‐G2 population, which was significantly higher than that in meio‐G0 population. In the meio‐G1 and meio‐G2 populations, correlation of seven growth traits with the CC genotype was significantly higher than that with the TT and TC genotypes in the c.1462C > T locus ( p  < .05). These results suggested that the CC genotype in the c.1462C > T locus could be an advantage mutation that stably affects the growth of different generations of this fish. It may be used as a potential molecular marker for gene‐assisted selection to improve a range of growth traits in topmouth culter.